Using WebCT to teach grammar selectively - Vance, Kathleen (HERMES - Journal of Language and Communication in Business, 2003)
Teachers of business and technical communication are supposed to teach grammar, but only to a limited extent, according to the literature. Technology program faculty at the British Columbia Institute of Technology and employers of graduates want grammar to be taught, along with an ever-expanding list of other employment-related communication skills. In response to these demands, a series of eight mini grammar lessons was developed for students in four technology programs. The software WebCT was used to facilitate the development and delivery of the lessons, which formed a component of the students’ business and technical communication course. Exercises, self-tests, and quizzes used sentences from workplace documents from the students’ technologies in order to hold the students’ attention and to validate the study of language. For students, this online component proved to be an attractive feature of their course.